Bidens biternata (Lour.) Merr. and Sherff Whole Plant Extract Fractions Inhibit the Growth of a Panel of Pathogenic Bacteria - Duan, Xu You; Cock, Ian Edwin (Pharmacognosy Communications, 2026)
Introduction: Bidens biternata (Lour.) Merr. and Sherff is used in several medicinal systems (including traditional Chinese medicine) for multiple purposes, including to treat bacterial infections. Despite this, B. biternata extracts, fractions and isolated compounds have not been rigorously examined for antibacterial properties against many pathogens. Materials and Methods: The antimicrobial activity of B. biternata whole plant extracts was investigated by disc diffusion assays and the MIC values were determined using liquid dilution assays against a panel of pathogenic bacteria. Toxicity was determined using the Artemia franciscana nauplii and HDF proliferation toxicity bioassays. Results: Fractions prepared from an ethanolic B. biternata whole plant extract inhibited the growth of a panel of bacterial species. Growth of both gram positive and gram negative bacteria was inhibited by the fractions, although the gram negative bacteria were substantially more susceptible to the extracts than the gram positive bacteria were. The 100% methanolic fraction prepared from the ethanolic B. biternata whole plant extract was a substantially better antibacterial agent compared to the other fractions. The 100% methanolic fraction was a strong inhibitor of P. aeruginosa and S. newport, with MIC values substantially <1000 μg/mL. This fraction also was a noteworthy inhibitor of A, faecalis, E. coli and S. pyogenes growth. Furthermore, all of the B. biternata fractions were nontoxic in the Artemia nauplii and human dermal fibroblast toxicity assays, indicating their safety for therapeutic use. Conclusion: The lack of toxicity of the B. biternata whole plant extracts and their growth inhibitory bioactivity against a panel of pathogenic bacteria partially validate the traditional usage of this species to treat bacterial diseases and indicates their potential in the development of antiseptic agents.
Keywords: Antibacterial Activity; Antibiotic-Resistant Bacteria; Asteraceae; Medicinal Plants; Spanish needles; Toxicity